RETRACTED: Principles of ontophylogenetic development of artificial general intelligence systems based on multi-agent neurocognitive architectures - Anchekov M.I.; Apshev A.Z.; Bzhikhatlov K.Ch.; Kankulov S.A.; Nagoev Z.V.; Nagoeva O.V.; Pshenokova I.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001